The Archipelago Outlook as the Foundation for Sustainable National Development - Zahwalia, Laila Nur (PT Keberlanjutan Strategis Indonesia, 2026)
Sustainable national development aims to improve the overall welfare of society without compromising the ability of future generations to meet their needs. This study examines the challenges faced by Indonesia in realizing sustainable development using a literature review from various related journals. The results of the study indicate that the implementation of sustainable development in Indonesia still faces several major obstacles, including weak coordination between government agencies, limited funding, development inequality between regions, low public awareness of the environment, and the threat of environmental damage and climate change. In addition, the quality of human resources and the availability of environmentally friendly technologies are also inhibiting factors. This study emphasizes that the success of sustainable development requires synergy between the government, society, the education sector, and the private sector, as well as the implementation of the Archipelago Outlook as a guideline in planning fair, equitable, and ecological development. By overcoming these challenges, Indonesia has the opportunity to realize inclusive and sustainable national development.